With Needle and Brush : Schoolgirl Embroidery from the Connecticut River Valley, 1740–1840 - Huber, Carol (Antique needlework dealer) (Book collections on Project MUSE., 2011)
First book to explore schoolgirl needlework of the Connecticut River Valley.